WebGE – Web-based groupware for education / Foong Yew Hong - Foong , Yew Hong (2004)
While group learning methods such as group assignments, forum and problem-based learning are increasingly being implemented in the education field, a variety of groupware tools such as email, online-forum and real-time chatting are used to replace or supplement the conventional face-to-face group learning processes. However, these tools are not particularly designed for education purpose and have some limitations. This study presents an integrated, full-fledge system, namely Web-based Groupware for Education (WebGE), for supporting the group learning processes. In this system, virtual groups are formed and information is shared within the group. Besides providing the commonly used groupware functions such as online discussion, real-time chatting, emailing, photos posting and files sharing, the course teachers also can use the specifically designed features such as assignment management, self-test, member progress, events management, polling, course material management and so forth. In simple words, WebGE is a complete online group learning system. WebGE was built based on the famous Unified Process, which uses object-oriented paradigm as the basis of software development. The implemented technologies are the state-of-the-art Microsoft ASP.Net with VB.Net and also the Microsoft SQL Server 2000. By using the latest technologies, the reliability and performance of WebGE can well be guaranteed.